Impact of Postdischarge Bleeding on Long-Term Mortality in Percutaneous Coronary Intervention Patients Taking Oral Anticoagulants. Issue 3 (September 2019) - Yoshida, Ruka; Ishii, Hideki; Morishima, Itsuro; Tanaka, Akihito; Morita, Yasuhiro; Takagi, Kensuke; Yoshioka, Naoki; Hirayama, Kenshi; Iwakawa, Naoki; Tashiro, Hiroshi; Kojima, Hiroki; Mitsuda, Takayuki; et al.
Abstract : Abstract: Although postdischarge bleeding (PDB) is known to negatively affect long-term outcome in patients undergoing percutaneous coronary intervention (PCI) with antiplatelet therapy (APT), the prognostic importance of PDB in patients who require both oral anticoagulants (OACs) and APT has not been fully elucidated. Among 3718 consecutive patients who underwent PCI, 302 patients were treated with both OACs and APT. We evaluated the association between PDB and 3-year all-cause mortality, as estimated by a time-updated Cox proportional hazard regression model. We performed nearest-neighbor matching on the propensity score to adjust the differences in baseline characteristics. Among 302 patients treated with OACs and APT, PDB was observed in 98 patients at a median time of 239 days. Patients experienced PDB had significantly higher incidence of 3-year all-cause mortality in the overall cohort and 94 propensity-score–matched pairs (hazard ratio 6.21, 95% confidence interval 3.29–11.72, P < 0.0001; and hazard ratio 6.13, 95% confidence interval 2.68–14.02, P < 0.0001, respectively). The risk of subsequent mortality was the highest within 180 days after PDB (58.3% within 180 days and 75.0% within 1 year). In conclusion, PDB was significantly associated with long-term mortality in patients taking both OACs and APT after PCI. Abstract : Supplemental Digital Content is Available in the Text.